Cold stress triggers premature fruit abscission through ABA-dependent signal transduction in early developing apple. - Youngsuk Lee; Van Giap Do; Seonae Kim; Hunjoong Kweon; Tony K McGhie (PLoS ONE)
Fruit abscission is a complex physiological process that is regulated by internal and environmental factors. During early development, apple fruit are exposed to extreme temperature fluctuations that are associated with premature fruit drop; however, their effect on fruit abscission is largely unknown. We hypothesized that fruit abscission is triggered by cold stress and investigated the molecular basis of premature fruit drop using RNA-Seq and metabolomics data from apple fruit undergoing abscission following cold stress in the field. Genes responsive to abscisic acid signaling and cell wall degradation were upregulated during abscission, consistent with the increased abscisic acid concentrations detected by liquid chromatography-mass spectrometry. We performed ex vivo cold shock experiments with excised tree subunits consisting of a branch, pedicel, and fruit. Abscission induction occurred in the cold-stressed subunits with concurrent upregulation of abscisic acid biosynthesis (MdNCED1) and metabolism (MdCYP707A) genes, and ethylene biosynthesis (MdACS1) and receptor (MdETR2) genes in the pedicel. Another key finding was the activation of cytoplasmic streaming in abscission-zone cells detected by electron microscopy. Our results provide a novel insight into the molecular basis of fruit abscission physiology in response to cold stress in apple.